Kriging-based optimization design for a new style shell with black box constraints. Issue 3 (September 2017) - Dong, Huachao; Song, Baowei; Wang, Peng
Complex engineering applications generally have the black box and computationally expensive characteristics. Surrogate-based optimization algorithms can effectively solve expensive black box optimization problems. This paper employs the kriging predictor to construct a surrogate model and uses an initial multistart optimization process to realize the global search on this kriging model. Based on a proposed trust region framework, a local search is carried out around the current promising solution. The whole optimization algorithm is implemented to solve a new style shell design of the autonomous underwater vehicle. Based on finite element analysis, buoyancy–weight ratio, maximum von Mises stress, and buckling critical load of the new style shell are calculated and stored as expensive sample values to construct the kriging model. Finally, the better design parameters of the new shell are obtained by this proposed optimization algorithm. In addition, compared with the traditional shell, the new shell shows the stronger stability and better buoyancy–weight ratio.